Synergistic antibacterial effect of copper and silver nanoparticles and their mechanism of action - Grigory Vasiliev; Anna-Liisa Kubo; Heiki Vija; Anne Kahru; Denys Bondar; Yevgen Karpichev; Olesja Bondarenko (Scientific Reports, 2023)
Abstract Bacterial infections are one of the leading causes of death worldwide. In the case of topical bacterial infections such as wound infections, silver (Ag) has historically been one of the most widely used antibacterials. However, scientific publications have demonstrated the adverse effects of silver on human cells, ecotoxicity and insufficient antibacterial effect for the complete elimination of bacterial infections. The use of Ag in the form of nanoparticles (NPs, 1–100 nm) allows to control the release of antibacterial Ag ions but is still not sufficient to eliminate infection and avoid cytotoxicity. In this study, we tested the potency of differently functionalized copper oxide (CuO) NPs to enhance the antibacterial properties of Ag NPs. The antibacterial effect of the mixture of CuO NPs (CuO, CuO–NH2 and CuO–COOH NPs) with Ag NPs (uncoated and coated) was studied. CuO and Ag NP combinations were more efficient than Cu or Ag (NPs) alone against a wide range of bacteria, including antibiotic-resistant strains such as gram-negative Escherichia coli and Pseudomonas aeruginosa as well as gram-positive Staphylococcus aureus, Enterococcus faecalis and Streptococcus dysgalactiae. We showed that positively charged CuO NPs enhanced the antibacterial effect of Ag NPs up to 6 times. Notably, compared to the synergy of CuO and Ag NPs, the synergy of respective metal ions was low, suggesting that NP surface is required for the enhanced antibacterial effect. We also studied the mechanisms of synergy and showed that the production of Cu+ ions, faster dissolution of Ag+ from Ag NPs and lower binding of Ag+ by proteins of the incubation media in the presence of Cu2+ were the main mechanisms of the synergy. In summary, CuO and Ag NP combinations allowed increasing the antibacterial effect up to 6 times. Thus, using CuO and Ag NP combinations enables to retain excellent antibacterial effects due to Ag and synergy and enhances beneficial effects, since Cu is a vital microelement for human cells. Thus, we suggest using combinations of Ag and CuO NPs in antibacterial materials, such as wound care products, to increase the antibacterial effect of Ag, improve safety and prevent and cure topical bacterial infections.